Canopy density effects on particulate matter attenuation coefficients in street canyons during summer in the Wuhan metropolitan area. (1st November 2020) - Wang, Xiaoshuang; Teng, Mingjun; Huang, Chunbo; Zhou, Zhixiang; Chen, Xiaoping; Xiang, Yang
Abstract: Changes in vegetation traits influence the particulate pollution mitigating effects of trees in street canyons; however, it remains unclear whether tree canopy density (i.e. the proportion of the street floor covered by the vertical projection of the tree canopy) promotes or reduces this effect. A 12-day field experiment was conducted in four representative street canyons to examine the mitigating effects of street trees on particulate matter (PM) for PM1, PM2.5, PM4, PM7, PM10, and total suspended particles (TSP) among four canopy density treatments, including (1) open spaces and areas with (2) sparse (≤35%), (3) medium (35–70%) and (4) dense (≥70%) canopy densities. The results showed that canopy density is the dominant vegetation trait that affects PM dispersion, with peak decreases occurring at a canopy density of 30%. The particulate matter attenuation coefficient (PMAC) indicates the PM reduction capability of trees. The PMAC of each particle size class correlated negatively with canopy density and TSP (<100 μm) showed the greatest attenuation. In relation to open space treatment, a canopy density range 30–36% showed the largest reductions in the PM10 and TSP concentrations of 26.75% and 27.49%, respectively. And for the PM2.5 concentration, a canopy density range 24–36% exhibited the largest reduction (7.44%). It was also concluded that sparse canopy density is optimal for trees in areas with high PM concentration. Medium canopy density also promotes pollutant dispersion (especially PM2.5 ), while dense canopy density causes air quality deterioration. This study will provide new insights into the response of atmospheric PM spatial dispersion to the characteristics of tree cover in street canyons, as well as the regulation mechanism of this response. By investigating this issue under different scenarios, this study aims to contribute to the quantitative tree planting design in urban planning. Graphical abstract: Image 1 Highlights: Trees morphological features affected the dispersion of particulate matter in street canyons.